2013
DOI: 10.1371/journal.pone.0054266
|View full text |Cite
|
Sign up to set email alerts
|

Integrating HIV Care into Primary Care Services: Quantifying Progress of an Intervention in South Africa

Abstract: BackgroundIntegration of human immunodeficiency virus (HIV) care into primary care services is one strategy proposed to achieve universal access to antiretroviral treatment (ART) for HIV-positive patients in high burden countries. There is a need for controlled studies of programmes to integrate HIV care with details of the services being integrated.MethodsA semi-quantitative questionnaire was developed in consultation with clinic staff, tested for internal consistency using Cronbach's alpha coefficients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Decentralization of HIV care has been pursued by numerous sub-Saharan African (SSA) countries (see, e.g., Fayorsey et al, 2013; Pfeiffer et al, 2010; Topp et al, 2013; Uebel, Joubert, Wouters, Mollentze, & van Rensburg, 2013; World Health Organization, 2013) and is advocated by the President’s Emergency Plan for AIDS Relief (PEPFAR) as a means of expanding coverage, co-utilizing services for HIV and other illnesses, and improving engagement and retention in care (PEPFAR, 2009; Gilks et al, 2006; Mulamba et al, 2010). While several implementation studies (Mutemwa et al, 2013; Topp et al, 2013; Uebel et al, 2013) described efficiency gains due to decentralization and integration of HIV care with care for other conditions, little is known about changes in patients’ care-seeking behaviors in response to the availability of additional treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decentralization of HIV care has been pursued by numerous sub-Saharan African (SSA) countries (see, e.g., Fayorsey et al, 2013; Pfeiffer et al, 2010; Topp et al, 2013; Uebel, Joubert, Wouters, Mollentze, & van Rensburg, 2013; World Health Organization, 2013) and is advocated by the President’s Emergency Plan for AIDS Relief (PEPFAR) as a means of expanding coverage, co-utilizing services for HIV and other illnesses, and improving engagement and retention in care (PEPFAR, 2009; Gilks et al, 2006; Mulamba et al, 2010). While several implementation studies (Mutemwa et al, 2013; Topp et al, 2013; Uebel et al, 2013) described efficiency gains due to decentralization and integration of HIV care with care for other conditions, little is known about changes in patients’ care-seeking behaviors in response to the availability of additional treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…While several implementation studies (Mutemwa et al, 2013; Topp et al, 2013; Uebel et al, 2013) described efficiency gains due to decentralization and integration of HIV care with care for other conditions, little is known about changes in patients’ care-seeking behaviors in response to the availability of additional treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…166 Developing quality indicators for NCD and HIV outcomes will assist in programmatic feedback and assessment of these potential tradeoffs. 166-169 …”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Emerging data within the field of primary care, however, provide evidence of the incremental benefit possible through integrated models. In South Africa, Uebel and colleagues reported small but significant reductions in mortality at facilities that scored high for total integration, ART integration (i.e., care provided by all nurses in the facility), and internal integration (i.e., care provided by all nurses in the HIV treatment unit) (17, 18). In Zambia, Topp, et al demonstrated increased time spent by providers during non-HIV clinic visits following integration of HIV services in the primary care setting, highlighting the potential for collateral health benefits (19).…”
Section: Why Integrate?mentioning
confidence: 99%